2021
DOI: 10.3390/en14196066
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of Liquid-Liquid Flows in Micro Channels and Its Influence on Transport Properties: A Review

Abstract: Hydrodynamics plays a major role in transport of heat and mass transfer in microchannels. This includes flow patterns and flow regimes in which the micro-channels are operated. The flow patterns have a major impact the transport properties. Another important aspect is the pressure drop in micro-channels. In the present review, the experimental and Computational Fluid Dynamics (CFD) studies covering all the above aspects have been covered. The effect of geometrical parameters like shape of channel, channel size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 108 publications
0
13
0
Order By: Relevance
“…It should be noted that the slug flow pattern is a steady and effective pattern for mass transfer. The considerable mass transfer in this flow pattern is attributed to the internal circulation in the slugs and the high interfacial area available for the mass transfer. , …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…It should be noted that the slug flow pattern is a steady and effective pattern for mass transfer. The considerable mass transfer in this flow pattern is attributed to the internal circulation in the slugs and the high interfacial area available for the mass transfer. , …”
Section: Resultsmentioning
confidence: 89%
“…The considerable mass transfer in this flow pattern is attributed to the internal circulation in the slugs and the high interfacial area available for the mass transfer. 59,60 3.1.2. Smooth Annular.…”
Section: Flow Patternmentioning
confidence: 99%
“…Excellent reviews focusing on hydrodynamics in micro‐channels have given detailed descriptions of flow patterns and pressure drop. [ 9–11 ] In the present review, we briefly describe the flow patterns that have been reported by previous investigators in microchannels. Typical geometries used for studies in micro‐channels are shown in Figure 1.…”
Section: Hydrodynamics Of Liquid–liquid Flows In Micro‐channelsmentioning
confidence: 97%
“…F I G U R E 4 Prominent regime maps available in the literature (Reproduced with permission from Ganguli and Pandit [10] ): (A) Wu et al, [20] (B) Yagodnitsyna et al, [16] (C) Kashid and Kiwi-Minsker, [21] (D) Foroughi and Kawaji, [22] and (E) Zhang et al [23] other, which segregates into a higher number of segments of the dispersed and continuous phases. Another way to vary interfacial area is to vary the ratio of inlet flow rates.…”
Section: Mass Transfer In Lle In Micro-channels and Effects Of Variou...mentioning
confidence: 99%
“…The article [8] entitled "Hydrodynamics of Liquid-Liquid Flows in Micro Channels and Its Influence on Transport Properties: A Review" is a review article on heat and mass transport in microchannels, including flow patterns and typical flow regimes in microchannels. The article discusses both experimental and computational research.…”
Section: A Short Review Of the Contributions In This Issuementioning
confidence: 99%